Comparing the effects of ketorolac and Paracetamol on postoperative pain relief after coronary artery bypass graft surgery. A randomized clinical trial - Javaherforooshzadeh, Fatemeh (J Cardiothorac Surg, 2020)
INTRODUCTION: Pain management after coronary artery bypass graft (CABG) surgery remains challenging. OBJECTIVE: This study aimed to compare the effects of Ketorolac and Paracetamol on postoperative CABG pain relief. METHOD: This double-blind randomized clinical trial study was conducted in Ahvaz, Iran, from September 2018–December 2019. Two consecutive groups of 60 patients undergoing elective on-pump coronary artery bypass graft surgery. INTERVENTION: The patients were divided into 0.5 mg/kg of ketorolac mg/dl and 10 mg/kg of Paracetamol after surgery for pain management. Primary outcomes were: visual analog pain scale (VAS) at the time point immediately after extubation (baseline) and at 6, 12, 24 and 48 h and the total dose of morphine consumption. Secondary outcomes included the hemodynamic variables, weaning time, chest tube derange, in-hospital mortality and myocardial infarction. Statistical analysis: The data were analyzed using SPSS version 22(SPSS, Chicago, IL). The Mann-Whitney U-test was used to compare demographic data, VAS scores, vital signs, and side effects. Repeated measurements were tested within groups using Friedman’s ANOVA and the Wilcoxon rank-sum test. Values were expressed as means ± standard deviations. Statistical significance was defined as a p-value < 0.05. RESULTS: Compared with baseline scores, there were significant declines in VAS scores in both groups throughout the time sequence (P< 0.05). The statistical VAS score was slightly higher in the Paracetamol group at most time points, except for the time of 6 h. However, at 24 and 48 h, the VAS score in group Paracetamol was significantly higher than in group Ketorolac. There were no significant differences between groups about hemodynamic variables. CONCLUSION: The efficacy of ketorolac is comparable to that of Paracetamol in postoperative CABG pain relief. TRIAL REGISTRY: IRCT20150216021098N5. Registered at 2019-09-12.